EVALUASI ADMINISTRASI DAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KUALITAS MASA DEPAN LEMBAGA PENDIDIKAN ISLAM - Azzahra, Titah Amalia; Sabila, Thoharotus; Az-Zahra, Fika Aulia; Wulandari, Nur Rahayu; Kurniawan, Ahmad Iqbal; Adawiyah, Robi'atul; Mardiyah (Institut Ummul Quro Al-Islami Bogor, 2026)
Improving the quality of Islamic educational institutions has become an important necessity amid globalization and technological developments. This study aims to analyze the contribution of administrative evaluation and educational supervision in improving the quality of Islamic educational institutions. The research employs a qualitative approach using a library research method through the analysis of books, journals, and relevant scientific articles. Data were analyzed using descriptive content analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that administrative evaluation plays an important role in improving institutional management, particularly in planning, program implementation, and data-based supervision. Educational supervision from an Islamic perspective functions not only as a control mechanism but also as a humanistic and collaborative professional development process grounded in the values of amanah, sincerity, and justice. The integration of evaluation and supervision contributes positively to improving teachers’ competencies, strengthening public trust, and enhancing the competitiveness of Islamic educational institutions. However, its implementation still faces challenges, such as limited human resources and suboptimal use of technology. Therefore, the development of sustainable digital-based evaluation and supervision systems is needed